Family health tasks and childhood stunting in primary care: A Cross-Sectional Study in Indonesia - Isymiarni Syarif; Wahyuni Langelo; Jukarnain Jukarnain; Andi Nursiah; Nur Masita (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Stunting remains a major public health problem in low- and middle-income countries, including Indonesia, and is influenced by biological, environmental, and behavioral factors within the family context. Evidence examining the role of comprehensive family health task performance in relation to stunting severity is still limited. To examine the association between family health task performance and the degree of stunting among children aged 0–24 months attending a primary health care center. Research Methodology: An analytical cross-sectional study was conducted among 120 families with stunted children in the catchment area of Bantimurung Primary Health Center, South Sulawesi, Indonesia. Family health task performance was assessed using a validated questionnaire covering five domains: recognizing health problems, making health decisions, caring for sick family members, modifying the home environment, and utilizing health facilities. Stunting severity was determined using height-for-age z-scores. Data were analyzed using descriptive statistics and Spearman’s rank correlation. Results: Family health task performance was significantly and negatively correlated with stunting severity (ρ = −0.341; p < 0.05). Utilization of health facilities (ρ = −0.421; p < 0.01) and environmental modification (ρ = −0.356; p < 0.05) showed the strongest associations with reduced stunting severity. Low birth weight and non-exclusive breastfeeding were also significantly associated with more severe stunting. Conclusion: Better family health task performance, particularly in engaging primary health services and maintaining a healthy home environment, is associated with less severe stunting. Strengthening family-centered interventions in primary care is essential to reducing the severity of stunting in early childhood